2023
DOI: 10.3390/cimb46010009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Somatic Mutations in the TCGA-LIHC Whole Exome Sequence to Identify the Neoantigen for Immunotherapy in Hepatocellular Carcinoma

Swetha Pulakuntla,
Khajamohiddin Syed,
Vaddi Damodara Reddy

Abstract: There are numerous clinically proven methods for treating cancer worldwide. Immunotherapy has been used to treat cancer with significant success in the current studies. The purpose of this work is to identify somatically altered target gene neoantigens and investigate liver cancer-related immune cell interaction and functional changes for potential immunotherapy in future clinical trials. Clinical patient data from the Cancer Genome Atlas (TCGA) database were used in this investigation. The R maf utility packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have demonstrated that peptides originating from tumor-specific mRNA splicing events possess the capability to interact with MHC class I (MHC I) molecules, acting as neoepitopes ( 44 , 45 ). A comprehensive The Cancer Genome Atlas (TCGA) study across various cancers suggested the involvement of alternative splicing programs in neoantigen generation by pinpointing cancer-specific exon-exon junctions and validating the presence of splicing-derived peptides through proteomics databases ( 46 , 47 ). Furthermore, intron retention has been highlighted as a crucial mechanism for neoantigen prediction, as numerous intron-retaining neoantigens have been identified through transcriptome sequencing and mass spectrometry analyses ( 48 ).…”
Section: Alternative Splicing As the Source Of Tumor Neoantigensmentioning
confidence: 99%
“…Recent studies have demonstrated that peptides originating from tumor-specific mRNA splicing events possess the capability to interact with MHC class I (MHC I) molecules, acting as neoepitopes ( 44 , 45 ). A comprehensive The Cancer Genome Atlas (TCGA) study across various cancers suggested the involvement of alternative splicing programs in neoantigen generation by pinpointing cancer-specific exon-exon junctions and validating the presence of splicing-derived peptides through proteomics databases ( 46 , 47 ). Furthermore, intron retention has been highlighted as a crucial mechanism for neoantigen prediction, as numerous intron-retaining neoantigens have been identified through transcriptome sequencing and mass spectrometry analyses ( 48 ).…”
Section: Alternative Splicing As the Source Of Tumor Neoantigensmentioning
confidence: 99%